Antioxidant Activity Test of Extract And Fractions of Red Guava (Psidium guajava L.) Peel and Fruit - Monica; Rohmana, Vivin Marwiyati; Pratama, Kharisma Jayak (JURNAL BIOSAINS, 2025)
Red guava (Psidium guajava L.) contains natural antioxidants that help neutralize free radicals originating from radiation, pollution, and harmful chemicals. This study aimed to identify secondary metabolites and determine the IC₅₀ values of ethanol extract and various fractions of red guava peel and fruit. Four solvents were used ethanol extract, ethyl acetate fraction, n-hexane fraction, and water fraction. Each sample was tested at concentrations of 20, 40, 60, 80, and 100 ppm. Vitamin C, at concentrations of 2, 4, 6, 8 and 10 ppm, served as a positive control. Antioxidant activity was evaluated using the DPPH method with a UV-Vis spectrophotometer at a wavelength of 516 nm and an incubation time of 30 minutes. Phytochemical screening showed that all extracts contained alkaloids, flavonoids, and tannins. The IC₅₀ values obtained were: ethanol extract peel 62,4719 ppm, ethanol extract fruit 44,0035 ppm, ethyl acetate fraction peel 56,7955 ppm, ethyl acetate fraction fruit 46,4394 ppm, n-hexane fraction peel 113,9311 ppm, n-hexane fraction fruit 114,4767 ppm, water fraction peel 104,0284 ppm, and water fraction fruit 76,5801 ppm.